A LINGUISTIC STUDY OF NEWSPAPER HEADLINES IN ENGLISH NEWSPAPERS PUBLISHED IN LAOS - Assoc. Prof. Dr. Phan Văn Hòa (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
For this very reason I chose to work on the subject of newspaper headlines with the hope that results of the study can help newspaper readers overcome this difficulty in comprehending them.